Kreativitas Dan Inovasi Dalam Pemanfaatan Limbah Karung Goni Untuk Kerajinan Tempat Penyimpanan - Fibria Mika Lapian; Gabhirela Asni Nganul; Lian Vanessa Lotulun; Arnoldus Yansen Bili; Ilham Nata Prayoga; Fensca F. Lahallo (CV. ITTC INDONESIA, 2025)
The utilization of jute sack waste as a base material for crafts has great potential in supporting environmentally friendly movements and increasing the economic value of the community. This research aims to explore the creativity and innovation in processing jute sack waste into storage craft products that have aesthetic value and practical functions. The research method used is descriptive qualitative with data collection techniques through observation and documentation of local craftsmen involved in the production of these crafts. The research results show that the creativity of craftsmen in designing motifs, shapes, and combinations of complementary materials plays a significant role in increasing the attractiveness of the product. Innovation is also seen from the use of simple but effective processing techniques, which makes the product not only valuable in art but also has competitiveness in the market. This research concludes that the creative and innovative utilization of jute sack waste can be a solution for reducing textile waste while opening up new economic opportunities for the community.